Caracterización dendrológica de las especies forestales más aprovechadas en la región sur del Ecuador - Loja Chalán, Angel Fernando (2015)
This research was conducted in the southern region of the Ecuador, in the provinces of El Oro, Loja and Zamora Chinchipe, between the months of April 2012 to July 2014. The dendrologic characterization of the most important forest species in the southern region of Ecuador, was conducted using surveys to owners of deposits of timber, in order to know the species most commercialized in the three provinces. Visits were also made to different farms to meet timber species, making the collection of botanical specimens and take pictures of them. The botanical samples were taken to Reinaldo Espinosa Herbarium of the National University of Loja, there pressing is performed, drying, taxonomic identification and botanical description of each species. Some species failed to identify within the herbal Loja, so the samples to the National Herbarium of Ecuador in Quito, where their identification was made. The results obtained show that in the southern region of Ecuador lot of timber species is marketed, among them: Vochysia duquei, Cordia alliodora, Otoba parvifolia, Trichilia sp, Cedrelinga cateniformis, Tabebuia chrysantha, Ficus obtusifolia, Poulsenia armata, Pleurothyrium cuneifolium, Cabralea canjerana; among others. In addition, some species such as Cedrela odorata and Swietenia macrophylla, are in closed, but still, still marketed in many deposits in the region. The study found that in the southern region of Ecuador there are 96 species in trade, but only 59 species collected and identified. The information gathered at field level and literature of the 59 species were captured in a document known as the common name, scientific name appears "More exploited in the Southern Region of Ecuador Forest Species", the family, the density, the use of wood, dendrologic description and photographs of each species identified in the present study.